The Matysa Nyaya and The Conventional Danda System (Bhartiya Knowledge Systems, 2024)
The concept of danda, referring to punishment in general, has its roots in the Vedic period in India. It is believed that administering punishment for wrongdoing is necessary for the administration of justice in every society. The Ramayana and Manusmriti texts emphasize the appropriate use of danda for the progress of the kingdom and the satisfaction of its subjects. The Dharma Sastras also recognize the court of justice as the place where the study of the social, economic, and political interests of humanity takes place. This paper highlights the Matysa Nyaya system found in the Matysa Purana which contains strict guidelines for administering justice in Vedic times. Neglecting the use of punishment could lead to the oppression of vulnerable groups by those in power. Danda was considered to govern all subjects, protect everyone, and prevent one from sin. Therefore, danda played a crucial role in administering justice and maintaining social order in ancient India.